Direct visualization of the drug loading of single DNA origami nanostructures by AFM-IR nanospectroscopy - Hanke, Marcel; Grundmeier, Guido; Keller, Adrian (Nanoscale)
The efficient loading of DNA nanostructures with intercalating or groove-binding drugs is an important prerequisite for various applications in drug delivery. However, unambiguous verification and quantification of successful drug loading...
Keywords: General Materials Science

Real-Space Identification of Non-Noble Single Atomic Catalytic Sites within Metal-Coordinated Supramolecular Networks - Schulze Lammers, Bertram; López-Salas, Nieves; Stein Siena, Julya; Mirhosseini, Hossein; Yesilpinar, Damla; Heske, Julian Joachim; Kühne, Thomas; Fuchs, Harald; Antonietti, Markus; Mönig, Harry (ACS Nano)
Keywords: General Physics and Astronomy; General Engineering; General Materials Science

Surface Passivation and Detrimental Heat-Induced Diffusion Effects in RbF-Treated Cu(In,Ga)Se2 Solar Cell Absorbers - Elizabeth, Amala; Sahoo, Sudhir K.; Phirke, Himanshu; Kodalle, Tim; Kühne, Thomas; Audinot, Jean-Nicolas; Wirtz, Tom; Redinger, Alex; Kaufmann, Christian A.; Mirhosseini, Hossein; Mönig, Harry (ACS Applied Materials & Interfaces)
Keywords: General Materials Science

Fingerprints Indicating Superior Properties of Internal Interfaces in Cu(In,Ga)Se 2 Thin‐Film Solar Cells - Raghuwanshi, Mohit; Chugh, Manjusha; Sozzi, Giovanna; Kanevce, Ana; Kühne, Thomas; Mirhosseini, Hossein; Wuerz, Roland; Cojocaru‐Mirédin, Oana (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Ni-based electrocatalysts for unconventional CO2 reduction reaction to formic acid - Lepre, Enrico; Heske, Julian Joachim; Nowakowski, Michal; Scoppola, Ernesto; Zizak, Ivo; Heil, Tobias; Kühne, Thomas; Antonietti, Markus; López-Salas, Nieves; Albero, Josep (Nano Energy)
Keywords: Electrical and Electronic Engineering; General Materials Science; Renewable Energy; Sustainability and the Environment

Giant Orbital Anisotropy with Strong Spin–Orbit Coupling Established at the Pseudomorphic Interface of the Co/Pd Superlattice - Kim, Sanghoon; Pathak, Sachin; Rhim, Sonny H.; Cha, Jongin; Jekal, Soyoung; Hong, Soon Cheol; Lee, Hyun Hwi; Park, Sung‐Hun; Lee, Han‐Koo; Park, Jae‐Hoon; Lee, Soogil; Steinrück, Hans-Georg; et al. (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

The Influence of Heat Treatment on the Microstructure, Surface Roughness and Shear Tensile Strength of AISI 304 Clinch Joints - Zeuner, André Till; Ewenz, Lars; Kalich, Jan; Schöne, Sebastian; Füssel, Uwe; Zimmermann, Martina (Metals)
Clinching is the manufacturing process of joining two or more metal sheets under high plastic deformation by form and force closure without thermal support and auxiliary parts. Clinch connections are applicable to difficult-to-join hybrid material combinations, such as steel and aluminum. Therefore, this technology is interesting for the application of AISI 304 components, as this material is widely used as a highly formable sheet material. A characteristic feature of AISI 304 is its metastability, i.e., the face-centered cubic (fcc) γ-austenite can transform into a significantly stronger body-centered cubic (bcc) α’-martensite under plastic deformation. This work investigates the effect of heat treatment—a process that involves the formation of an oxidation layer on the sheet surface—on the forming process during joining and the resulting mechanical properties of clinch joints made from AISI 304. For this purpose, different joints made from non-heat treated and heat-treated sheets were examined using classical metallography and advanced SEM techniques, accompanied by further investigations, such as hardness and feritscope measurements. The shear tensile strength was determined, and the fracture behavior of the samples was investigated. Clear influences of heat-treatment-induced surface roughness on the joint geometry and strength were observed.
Keywords: General Materials Science; Metals and Alloys

Long-Term Behavior of Clinched Electrical Contacts - Kalich, Jan; Matzke, Marcus; Pfeiffer, Wolfgang; Schlegel, Stephan; Kornhuber, Ludwig; Füssel, Uwe (Metals)
Joining by forming operations presents powerful and complex joining techniques. Clinching is a well-known joining process for use in sheet metalworking. Currently, clinched joints are focusing on mechanically enhanced connections. Additionally, the demand for integrating electrical requirements to transmit electrical currents will be increased in the future. This integration is particularly important, for instance, in the e-mobility sector. It enables connecting battery cells with electrical joints of aluminum and copper. Systematic use of the process-specific advantages of this joining method opens up the possibility to find and create electrically optimized connections. The optimization for the transmission of electrical currents will be demonstrated for clinched joints by adapting the tool geometry and the clinched joint design. Based on a comparison of the electrical joint resistance, the limit use temperature is defined for the joining materials used based on the microstructural condition and the aging condition due to artificial aging. As a result of the investigations carried out, reliable current transmission at a constant conductor temperature of up to 120 °C can be achieved for clinched copper–copper joints. In the case of pure aluminum joints and mixed joints of aluminum and copper, long-term stable current transmission can be ensured up to a conductor temperature of 100 °C.
Keywords: General Materials Science; Metals and Alloys

Modelling and Simulation Strategies for Fluid–Structure-Interactions of Highly Viscous Thermoplastic Melt and Single Fibres—A Numerical Study - Gröger, Benjamin; Wang, Jingjing; Bätzel, Tim; Hornig, Andreas; Gude, Maik (Materials)
A virtual test setup for investigating single fibres in a transverse shear flow based on a parallel-plate rheometer is presented. The investigations are carried out to verify a numerical representation of the fluid–structure interaction (FSI), where Arbitrary Lagrangian–Eulerian (ALE) and computational fluid dynamics (CFD) methods are used and evaluated. Both are suitable to simulate flexible solid structures in a transverse shear flow. Comparative investigations with different model setups and increasing complexity are presented. It is shown, that the CFD method with an interface-based coupling approach is not capable of handling small fibre diameters in comparison to large fluid domains due to mesh dependencies at the interface definitions. The ALE method is more suited for this task since fibres are embedded without any mesh restrictions. Element types beam, solid, and discrete are considered for fibre modelling. It is shown that the beam formulation for ALE and 3D solid elements for the CFD method are the preferred options.
Keywords: General Materials Science

Investigations on Combined in situ CT and Acoustic Analysis during Clinching - Köhler, Daniel; Stephan, Richard; Kupfer, Robert; Troschitz, Juliane; Brosius, Alexander; Gude, Maik (Key Engineering Materials)
Clinching is a cost efficient method for joining components in series production. To assure the clinch point’s quality, the force displacement curve during clinching or the bottom thickness are monitored. The most significant geometrical characteristics of the clinch point, neck thickness and undercut, are usually tested destructively by microsectioning. However, micrograph preparation goes ahead with a resetting of elastic deformations and crack-closing after unloading. To generate a comprehensive knowledge of the clinch point’s inner geometry under load, in-situ computed tomography (CT) and acoustic testing (TDA) can be combined. While the TDA is highly sensitive to the inner state of the clinch point, it could detect critical events like crack development during loading. If such events are indicated, the loading process is stopped and a stepped in-situ CT of the following crack and deformation development is performed. In this paper, the concept is applied to the process of clinching itself, providing a detailed three-dimensional insight in the development of the joining zone. A test set-up is used which allows a stepwise clinching of two aluminium sheets EN AW 6014. Furthermore, this set-up is positioned within a CT system. In order to minimize X-ray absorption, a beryllium cylinder is used within the set-up frame and clinching tools are made from Si3N4. The actuator and sensor necessary for the TDA are integrated in the set-up. In regular process steps, the clinching process is interrupted in order to perform a TDA and a CT scan. In order to enhance the visibility of the interface, a thin tin layer is positioned between the sheets prior clinching. It is shown, that the test-set up allows a monitoring of the dynamic behaviour of the specimen during clinching while the CT scans visualize the inner geometry and material flow non-destructively.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Numerical fatigue life prediction of corroded and non-corroded clinched joints - Harzheim, Sven; Hofmann, Martin; Wallmersperger, Thomas (Mechanics of Advanced Materials and Structures)
Mechanical clinching is used to create lightweight hybrid structures. In order to estimate the service life of clinched components, its fatigue properties need to be known under different mechanical loading conditions. In addition to fatigue, corrosion is another factor that affects the fatigue life of clinched joints. In the literature, many corrosion and high-cycle fatigue damage models exist. However, little is known about how both phenomena interact in clinched joints. In this article, the influence of galvanic corrosion on clinched EN AW-6014/HCT590X + Z sheets on the fatigue life is investigated by means of numerical simulations and experimental results. An accurate prediction of the Wöhler lines of non-corroded and pre-corroded clinched specimens is shown.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science; General Mathematics; Civil and Structural Engineering

Experimental and Numerical Investigation on Manufacturing-Induced Pre-Strain on the Load-Bearing Capacity of Clinched Joints - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (Key Engineering Materials)
Background. Clinching is a conventional cold forming process in which two or more sheets can be joined without auxiliary parts. A pre-forming of the parts to be joined, which is introduced by previous manufacturing steps, has an influence on the joining result. When considering the suitability for joining with regard to the formability of the materials, the influence of the preforming steps must be taken into account. The influences of strain hardening and sheet thickness on the joining properties must be investigated. In this context, a Finite Element Method (FEM) based metamodel analysis of the clinching process was carried out in [1] to investigate the robustness of the clinching process with respect to the different material pre-strains. In [2], the method was extended to the load bearing simulation.Procedure. The metamodel from preliminary work based on various FE models, which predicts the load-bearing capacity of a clinched joint influenced by pre-straining, is compared here with experimental data and the accuracy of the metamodel prediction is discussed. For this purpose an experimental procedure was further develop which allows the preforming of metal sheets from which joining specimens can be separated with a certain degree of unidirectional deformation. In the study, the procedure for preparing the joint specimens and the results of the loading tests are presented. Different possible relevant pre-strain combinations are investigated and compared with the simulation results, to validate the FE models and choose suitable metamodel.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Nanoscale Conductive Sheets in Ferroelectric BaTiO3: Large Hall Electron Mobilities at Head-to-Head Domain Walls - Beccard, Henrik; Kirbus, Benjamin; Beyreuther, Elke; Rüsing, Michael; Bednyakov, Petr; Hlinka, Jiří; Eng, Lukas M. (ACS Applied Nano Materials)
Strongly charged head-to-head domain walls that are purposely engineered along the [110] crystallographic orientation into ferroelectric BaTiO3 single crystals have been proposed as intrinsically nanoscaled two-dimensional electron gases (2DEGs) because of their significant conductivity. Here, we quantify these 2DEG properties through dedicated Hall transport measurements in van der Pauw 4-point geometry, finding the electron mobility to reach around 400 cm2 (V s)^{−1}, while the two-dimensional charge density amounts to 7 × 103 cm^{–2}. We underline the necessity to take into account the thermal and geometrical misalignment offset voltages by evaluating the Hall resistance under magnetic field sweeps; otherwise, errors of several hundred percent in the derived transport parameters can occur.
Keywords: General Materials Science

Influence of heat treatment on the suitability for clinching of the aluminium casting alloy AlSi9 - Neuser, Moritz; Böhnke, Max; Grydin, Olexandr; Bobbert, Mathias; Schaper, Mirko; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
In many manufacturing areas, multi-material designs are implemented in which individual components are joined together to form complex structures with numerous joints. For example, in the automotive sector, cast components are used at the junctions of the body and joined with different types of sheet metal and extruded profiles. To be able to join structures consisting of different materials, alternative joining technologies have emerged in recent years. This includes clinching, which allows assembling of two or more thin sheet metal and casting parts by solely cold forming the material. Clinching the brittle and usually less ductile cast aluminium alloys remains a challenge because the brittle character of the cast aluminium alloys can cause cracks during the forming of the clinched joint. In this study, the influence of the heat treatment time of an aluminium casting alloy AlSi9 on the joinability in the clinching process is investigated. Specific heat treatment of the naturally hard AlSi9 leads to a modification of the eutectic microstructure, which can increase ductility. Based on this, it will be examined if specific clinching die geometries can be used, which achieve an optimized geometrical formation of the clinched joint. The load-bearing capacities of the clinched joints are determined and compared by shear tensile and head tensile tests. Furthermore, the joints are examined microscopically to investigate the influence of the heat treatment on the failure behaviour during the load-bearing tests as well as crack initiation within the joining process.
Keywords: Mechanical Engineering; General Materials Science

Insights into the decomposition of zirconium acetylacetonate using synchrotron radiation: Routes to the formation of volatile Zr-intermediates - Grimm, Sebastian; Baik, Seung-Jin; Hemberger, Patrick; Kasper, Tina; Kempf, Andreas M.; Atakan, Burak (Journal of Materials Research)
Abstract The thermal decomposition of Zr(acac) 4 is studied in a SiC-microreactor on the micro-second time scale. By utilizing synchrotron radiation and photoelectron photoion coincidence spectroscopy, six important zirconium intermediates, as for instance Zr(C 5 H 7 O 2 ) 2 (C 5 H 6 O 2 ), and Zr(C 5 H 6 O 2 ) 2 , are identified in the gas phase for the first time. The adiabatic ionization thresholds of intermediately formed zirconium species are estimated and the main products of their thermal decomposition, acetylacetone, acetylallene and acetone are characterized unambiguously and isomer-selectively. Based on all detected intermediates, we deduce the predominant pyrolysis pathways of the precursor in the temperature range from 400 to 900 K. Our findings are complemented by numerical simulations of the flow field in the microreactor, which show that the choice of dilution gas significantly influences the temperature profile and residence times in the microreactor, such that helium provides a more uniform flow field than argon and should preferentially be used. Graphical abstract Using a soft ionization method coupled to velocity map imaging (VMI), leads to valuable insights in the thermal decomposition of Zr(C 5 H 7 O 2 ) 4 , used in the synthesis of functional nanomaterials and ceramic coatings. Thanks to the use of a microreactor, important gas
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Functionality Study of an Optical Measurement Concept for Local Force Signal Determination in High Strain Rate Tensile Tests - Böhnke, Max; Unruh, Eduard; Sell, Stanislaw; Bobbert, Mathias; Hein, David; Meschut, Gerson (Key Engineering Materials)
Many mechanical material properties show a dependence on the strain rate, e.g. yield stress or elongation at fracture. The quantitative description of the material behavior under dynamic loading is of major importance for the evaluation of crash safety. This is carried out using numerical methods and requires characteristic values for the materials used. For the standardized determination of dynamic characteristic values in sheet metal materials, tensile tests performed according to the guideline from [1]. A particular challenge in dynamic tensile tests is the force measurement during the test. For this purpose, strain gauges are attached on each specimen, wired to the measuring equipment and calibrated. This is a common way to determine a force signal that is as low in vibration and as free of bending moments as possible. The preparation effort for the used strain gauges are enormous. For these reasons, an optical method to determine the force by strain measurement using DIC is presented. The experiments are carried out on a high speed tensile testing system. In combioantion with a 3D DIC high speed system for optical strain measurement. The elastic deformation of the specimen in the dynamometric section is measured using strain gauges and the optical method. The measured signals are then compared to validate the presented method. The investigations are conducted using the dual phase steel material HCT590X and the aluminum material EN AW-6014 T4. Strain rates of up to 240 s-1 are investigated.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Ni-based electrocatalysts for unconventional CO2 reduction reaction to formic acid - Lepre, Enrico; Heske, Julian; Nowakowski, Michal; Scoppola, Ernesto; Zizak, Ivo; Heil, Tobias; Kühne, Thomas D.; Antonietti, Markus; Lopez Salas, Nieves; Albero, Josep (Nano Energy)
Keywords: Electrical and Electronic Engineering; General Materials Science; Renewable Energy; Sustainability and the Environment

Synthesis and Characterization of Catalytically Active Au Core─Pd Shell Nanoparticles Supported on Alumina - Feng, Yanyue; Schaefer, Andreas; Hellman, Anders; Di, Mengqiao; Härelind, Hanna; Bauer, Matthias; Carlsson, Per-Anders (Langmuir)
A two-step seeded-growth method was refined to synthesize Au@Pd core@shell nanoparticles with thin Pd shells, which were then deposited onto alumina to obtain a supported Au@Pd/Al2O3 catalyst active for prototypical CO oxidation. By the strict control of temperature and Pd/Au molar ratio and the use of l-ascorbic acid for making both Au cores and Pd shells, a 1.5 nm Pd layer is formed around the Au core, as evidenced by transmission electron microscopy and energy-dispersive spectroscopy. The core@shell structure and the Pd shell remain intact upon deposition onto alumina and after being used for CO oxidation, as revealed by additional X-ray diffraction and X-ray photoemission spectroscopy before and after the reaction. The Pd shell surface was characterized with in situ infrared (IR) spectroscopy using CO as a chemical probe during CO adsorption–desorption. The IR bands for CO ad-species on the Pd shell suggest that the shell exposes mostly low-index surfaces, likely Pd(111) as the majority facet. Generally, the IR bands are blue-shifted as compared to conventional Pd/alumina catalysts, which may be due to the different support materials for Pd, Au versus Al2O3, and/or less strain of the Pd shell. Frequencies obtained from density functional calculations suggest the latter to be significant. Further, the catalytic CO oxidation ignition-extinction processes were followed by in situ IR, which shows the common CO poisoning and kinetic behavior associated with competitive adsorption of CO and O2 that is typically observed for noble metal catalysts.
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Ni-based electrocatalysts for unconventional CO2 reduction reaction to formic acid - Lepre, Enrico; Heske, Julian; Nowakowski, Michal; Scoppola, Ernesto; Zizak, Ivo; Heil, Tobias; Kühne, Thomas D.; Antonietti, Markus; López-Salas, Nieves; Albero, Josep (Nano Energy)
Keywords: Electrical and Electronic Engineering; General Materials Science; Renewable Energy; Sustainability and the Environment

Following carbon condensation by in situ TEM: towards a rational understanding of the processes in the synthesis of nitrogen-doped carbonaceous materials - Piankova, Diana; Kossmann, Janina; Zschiesche, Hannes; Antonietti, Markus; Lopez Salas, Nieves; Tarakina, Nadezda V. (Journal of Materials Chemistry A)
In situ TEM heating experiments combined with extensive chemical, structural and sorption analysis reveal the nanoscale mechanism of porosity formation in carbonaceous materials obtained directly from molecular precursors.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry